Associations between lifestyle behaviours and optimal wellbeing in a diverse sample of New Zealand adults. (December 2015) - Prendergast, Kate; Schofield, Grant; Mackay, Lisa
Abstract Background In positive psychology optimal wellbeing is considered a broad, multi-dimensional construct encompassing both feelings and functioning. Yet, this notion of wellbeing has not been translated into public health. The purpose of this study is to integrate public health and positive psychology to determine associations between lifestyle behaviours and optimal wellbeing in a diverse sample of New Zealand adults. Methods A web-based survey design was employed to collect data. Participants reported on their wellbeing and lifestyle behaviours including nutrition, exercise, sedentary behaviour, and sleep. Optimal wellbeing was calculated using a multi-dimensional scale designed to mirror the internationally recognised diagnostic criteria for mental disorders. Binary logistic regression was used to calculate associations between 10 lifestyle behaviours and optimal wellbeing. Results Of the total sample (n  = 9514), 24 % met the criteria for optimal wellbeing. Compared to reference groups, the association with optimal wellbeing was greater for those who reported exercising ≥7 times/week (odds ratio: 1.61, 95 % confidence interval: 1.22–2.13, p  < 0.01) and sitting "almost none of the time" (1.87, 1.01–3.29, p  < 0.01). Optimal wellbeing was lower for those reporting restless sleep "almost all of the time" (0.24, 95 % CI: 0.17–0.32p  < 0.01) and consuming sugary drinks 5–6 times/week (0.73, 95 % CI: 0.53–0.95, p  < 0.05). Conclusions Public health and positive psychology were integrated to provide support for a relationship between lifestyle behaviours and a multi-dimensional measure of optimal wellbeing. It is likely this relationship between lifestyle behaviours and optimal wellbeing is bidirectional giving rise to the debate that holistic approaches are needed to promote positive health.